Project-Based Learning: Principles, Characteristics, and Application in Teaching Grammar Rules - Masnun, Masnun; Munjiah, Ma'rifatul; Yasmar, Renti (Institut Agama Islam Negeri Curup, 2024)
This study aims to address the challenges of teaching grammar, which often relies on theoretical material with limited practical application, individual teaching methods, and a teacher-cantered approach. It proposes the use of project-based learning (PjBL) as a model to engage students actively and improve their understanding of grammar. The research, conducted at Nurul Ulum Islamic Religious School for Girls in Kebonsari, Malang, East Java, explores the implementation of the PjBL model in grammar instruction and the nature of the projects used in this context. The model comprises three main stages: pre-action (goal setting, tool selection, and time planning), action (assignment, planning, and evaluation), and post-action. During the action phase, students work collaboratively to construct sentences based on Qur'anic verses, with a specific focus on understanding grammatical rules such as the nominative case for nouns. The findings suggest that this approach fosters students’ initiative, independence, and cooperation while promoting responsibility in problem-solving tasks. This model enhances students' active participation and engagement, making grammar instruction more dynamic and contextually relevant.